Association Between Body Size and Composition and Erectile Dysfunction in Older Men: Osteoporotic Fractures in Men Study. Issue 1 (11th January 2013) - Garimella, Pranav S.; Paudel, Misti L.; Ensrud, Kristine E.; Marshall, Lynn M.; Taylor, Brent C.; Fink, Howard A.; for the Osteoporotic Fractures in Men (MrOS) Research Group
<x xml:space="preserve">Abstract</x> Objectives To examine the association between body size and composition and erectile dysfunction (ED) in older men. Design Cross‐sectional analysis of the Osteoporotic Fractures in Men study. Setting Six U.S. clinical sites. Participants Community‐dwelling men aged 65 and older. Measurements Body composition measures using anthropometry (body weight, body mass index (BMI)) and dual X‐ray absorptiometry (total body fat percentage, trunk fat percentage, ratio of trunk and total body fat). ED was assessed using the single‐item Massachusetts Male Aging Study (MMAS) scale and the five‐item International Index of Erectile Function questionnaire (IIEF‐5). Results In men completing the MMAS scale (n = 4, 108), prevalence of complete ED was 42%. In sexually active men completing the IIEF‐5 questionnaire (n = 1, 659), prevalence of moderate to severe ED was 56%. In multivariate‐adjusted analyses reporting prevalence ratios (PRs) and 95% confidence intervals (CIs), the prevalence of MMAS‐defined complete ED was significantly greater in men in the highest quartile of body weight (PR = 1.24, 95% CI = 1.16–1.34), total body fat percentage (PR = 1.25, 95% CI = 1.13–1.40), and trunk fat percentage (PR = 1.24, 95% CI = 1.15–1.38), and was greater in men with a BMI greater than 30.0 kg/m2 than in those with BMI of 22.0 to 24.9 kg/m2 (PR = 1.17, 95% CI = 1.05–1.31). Associations appeared similar for IIEF‐5–defined moderate to severe ED in analyses adjusted for age and study site. Conclusion In a cohort of older men, high body weight, BMI, and total body fat percentage were independently associated with greater prevalence of moderate to severe and complete ED. Future studies should investigate whether interventions to promote weight loss and fat loss will improve erectile function in older men.